Historical and Cultural Phenomenon of Children’s Everyday Life in the Programmes of Kazakh Radio of the Soviet Period - Assymova, D.; Zhalmagambetov, Y.; Khamidullina, D.; Astemes, G.; Kyrgyzkhan, G. (Journal of Posthumanism, 2025)
The purpose of this study was to highlight the content of radio programmes of Kazakh radio broadcasting for children, as an example of professional work on the education of the younger generation, from a modern perspective. The influence of audiovisual materials on the younger generation and their daily life, the formation of historical memory through images and associations. Analysis of the historical and cultural phenomenon of children’s radio programmes in Soviet Kazakhstan. The materials of the study were both archival and field sources, opinions of domestic radio journalists, from the funds of Kazakh radio in the chronological framework of the stated topic, as well as thematic publications of domestic and foreign scientists. The methods of research were taken methods and principles of dialectical logic, the principle of historicism, allowing to take into account the general political situation in the USSR and external factors, which allowed to build a coherent methodology of work. The results of the study: a step-by-step reconstruction of the evolution of the content of Soviet (Kazakh including) radio broadcasting, intended for a certain age (children and teenagers); identification of co-dependence of the all-union content with the content of radio air of the union and autonomous republics; clarification of the structure of Kazradio and personnel potential, individual biographies of masters of national radio broadcasting; analysis of critical concepts of foreign researchers and others. Accordingly, the scope of application of the research results extends to the preparation of lecture courses in universities, writing generalising works on the history of ‘children’s’ radio broadcasting in the republic in the Soviet period, recommendations for diversifying children’s radio air. The author comes to the conclusion about the significance of the problem of differentiation of media (radio) content in Independent Kazakhstan, for the professional promotion of national values in the children and youth environment.